P191 RISING INCIDENCE OF IRON DEFICIENCY ANEMIA AND ASSOCIATED COST OF CARE IN HOSPITALIZED PATIENTS OF INFLAMMATORY BOWEL DISEASE IN USA: NATIONWIDE ANALYSIS 2002–2014. (18th January 2018) - Khan, Zubair; Siddiqui, Nauman; Hasan, Syed; Sodeman, Thomas; Nawras, Ali
Abstract: Background: Extraintestinal complications are common in IBD, and are reported in more than 25% of patients. Anemia is one of the most common manifestations of IBD. One-third of patients with IBD have hemoglobin levels below 12 g/dL. Although ongoing blood loss from chronically inflamed intestinal mucosa and micronutrient deficiency (iron and B12) are the main mechanisms underlying the development of anemia in patients with IBD, chronic inflammation, hemolysis, and medication-induced myelosuppression may also play important roles. Methods: We analyzed the National Inpatient Sample (NIS) database for all subjects with discharge diagnosis of IBD (Ulcerative Colitis & Crohn's disease) with or without iron deficiency anemia (IDA) as primary or secondary diagnosis via ICD 9 codes during the period from 2002–2014. All analyses were performed with the use of SAS (version 9.4). Results: From 2002–2014 there were total 23834 discharges of Ulcerative Colitis (UC) patients and 31998 discharges of Crohn's Disease (CD) patients with IDA, constituting 9.8% & 7.4% discharges respectively. There was a rising trend of IDA in percentage of discharged patients of IBD from 7.4% in 2002 to 9.2% in 2014. Over the years the median length of stay decreased for IBD patients with and without IDA, but still the length of stay was more in IBD patients with IDA vs without IDA. On Multivariate regression analysis Male gender, age above 50, Hispanic race, small hospital, congestive heart failure, malignancy and metastatic disease were significant predictors of IDA in IBD. Conclusions: This analysis demonstrates the burden of IDA in patients of IBD. In a patient population with the predisposition for anemia, like patients with IBD, early diagnosis and management of iron deficiency can promptly reduce hospital visits, improve quality of life, reduce loss of work, and, ultimately, lower health care costs.